2018
DOI: 10.1016/s2214-109x(18)30126-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of community-level effects of intermittent preventive treatment for malaria in schoolchildren in Jinja, Uganda (START-IPT trial): a cluster-randomised trial

Abstract: SummaryBackgroundIntermittent preventive treatment (IPT) is a well established malaria control intervention. Evidence that delivering IPT to schoolchildren could provide community-level benefits is limited. We did a cluster-randomised controlled trial to assess the effect of IPT of primary schoolchildren with dihydroartemisinin-piperaquine (DP) on indicators of malaria transmission in the community, in Jinja, Uganda.MethodsWe included 84 clusters, each comprising one primary school and the 100 closest availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 28 publications
(42 reference statements)
1
57
0
Order By: Relevance
“…Malaria infection in school-aged children is mostly asymptomatic ( Walldorf et al, 2015 ; Nankabirwa et al, 2014 ; Nankabirwa et al, 2013 ; Yeka et al, 2015 ) making them reservoirs for transmission within their communities, at the cost of increased malaria related morbidities such as anaemia and impaired cognitive development ( Nankabirwa et al, 2014 ; Clarke et al, 2008 ; Nankabirwa et al, 2013 ; Maccario et al, 2017 ) in this age group. Given the high correlation shown ( r = 93%), targeted interventions such as (IPT) need to be expanded to school-aged children (IPTsc) since they are more likely to harbour malaria parasites compared to under-fives and pregnant women ( Walldorf et al, 2015 ; Staedke et al, 2018 ). This would likely reduce the parasite burden in children and boost the effectiveness of other control programs including IPTp and SMC ( Staedke et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Malaria infection in school-aged children is mostly asymptomatic ( Walldorf et al, 2015 ; Nankabirwa et al, 2014 ; Nankabirwa et al, 2013 ; Yeka et al, 2015 ) making them reservoirs for transmission within their communities, at the cost of increased malaria related morbidities such as anaemia and impaired cognitive development ( Nankabirwa et al, 2014 ; Clarke et al, 2008 ; Nankabirwa et al, 2013 ; Maccario et al, 2017 ) in this age group. Given the high correlation shown ( r = 93%), targeted interventions such as (IPT) need to be expanded to school-aged children (IPTsc) since they are more likely to harbour malaria parasites compared to under-fives and pregnant women ( Walldorf et al, 2015 ; Staedke et al, 2018 ). This would likely reduce the parasite burden in children and boost the effectiveness of other control programs including IPTp and SMC ( Staedke et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the high correlation shown ( r = 93%), targeted interventions such as (IPT) need to be expanded to school-aged children (IPTsc) since they are more likely to harbour malaria parasites compared to under-fives and pregnant women ( Walldorf et al, 2015 ; Staedke et al, 2018 ). This would likely reduce the parasite burden in children and boost the effectiveness of other control programs including IPTp and SMC ( Staedke et al, 2018 ). Recent evidence in Uganda demonstrated that with high coverage, implementation of IPTsc using Dihydroartemisinin-Piperaquine (DP) was effective in reducing community parasite prevalence and entomological inoculation rates ( Staedke et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations